2016
DOI: 10.1017/s0007114516001525
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Dietary Intake Assessment (e-DIA): relative validity of a mobile phone application to measure intake of food groups

Abstract: Automation of dietary assessment can reduce limitations of established methodologies, by alleviating participant and researcher burden. Designed as a research tool, the electronic Dietary Intake Assessment (e-DIA) is a food record in mobile phone application format. The present study aimed to examine the relative validity of the e-DIA with the 24-h recall method to estimate intake of food groups. A sample of eighty university students aged 19-24 years recorded 5 d of e-DIA and 3 d of recall within this 5-d per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 34 publications
3
48
0
2
Order By: Relevance
“…Twenty-four hour-recalls have been used as a reference method for two novel dietary assessment methods, namely My Meal Mate (MMM) [8] and Electronic dietary intake assessment (e-DIA) [24]. Results from both studies reported a mean EI comparable to 24-h dietary recalls, with Bland-Altman plots showing minimal bias but with wide limits of agreement [8, 24]. However, neither study assessed misreporting or accounted for under or over reporting of dietary intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four hour-recalls have been used as a reference method for two novel dietary assessment methods, namely My Meal Mate (MMM) [8] and Electronic dietary intake assessment (e-DIA) [24]. Results from both studies reported a mean EI comparable to 24-h dietary recalls, with Bland-Altman plots showing minimal bias but with wide limits of agreement [8, 24]. However, neither study assessed misreporting or accounted for under or over reporting of dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…Existing electronic food diaries have been evaluated using a variety of methods as the reference method including doubly-labelled water (DLW) [6, 21, 22], 24-h recalls [8, 23, 24], weighed food records [10, 25] and estimated food records [26, 27]. Each method has limitations; DLW because of its high cost, invasiveness, specialised equipment for analysis and the need for trained personnel [1].…”
Section: Introductionmentioning
confidence: 99%
“…Correlations were deattenuated and energy; BA analysis also done for macronutrient intakes and plots showed no evidence of systematic bias. Mean differences in dietary intakes between were small and not significant Rangan [ 41 ], 2016 Young adults; N = 80; 63% female; mean (SD) age = 21(0.5) years old c Electronic Dietary Intake Assessment (e-DIA); 5 days 0 3 x 24HR, conducted on random days Fruits, vegetables, grains, meat and alternatives, dairy and alternatives, discretionary foods, discretionary beverages, alcoholic beverages ρ = 0.69 for discretionary beverages to ρ = 0.88 for discretionary food and for alcoholic beverages Limits of agreement (e-DIA-24HR) ranged from −0.8 g (−124, 122) for meat and alternatives to 23.0 g (−293, 339) for discretionary beverages BA plots showed no evidence of systematic bias. Median differences in food group intakes were not significant.…”
Section: Resultsmentioning
confidence: 99%
“…O artigo de Rangan et al (2016) examinou a validade de uma ferramenta de avaliação da ingestão dietética eletrônica (e-DIA), comparada com um recordatório de 24 horas, a m de medir o consumo de grupos de alimentos em uma amostra de 80 estudantes universitários, havendo entre esses 50 mulheres com média de idade de 21 anos. Trata-se de um aplicativo de celular que registra digitalmente todos os alimentos e bebidas consumidos, sejam eles pesados ou estimados.…”
Section: Artigo Originalunclassified